Dopamine D2 receptors in the basolateral amygdala modulate erectile function in a rat model of nonorganic erectile dysfunction. (1st October 2018) - Chen, Guotao; Chen, Jianhuai; Yang, Baibing; Yu, Wen; Chen, Yun; Dai, Yutian
Abstract: Nonorganic erectile dysfunction is a problem with unknown central mechanisms. Changes in brain activity in the amygdala have been observed in human patients. This study aimed to investigate the dopamine system in the basolateral amygdala of male rats with nonorganic erectile dysfunction. We applied chronic mild stress to induce nonorganic erectile dysfunction. After exposure to chronic mild stress, the sucrose consumption test, sexual behaviour test and apomorphine test were used to select depression‐like rats with erectile dysfunction as nonorganic erectile dysfunction model rats. The sexual behaviour of these rats after central infusion of a dopamine D1/D2 receptor agonist/antagonist was observed. The expression levels of dopamine D1/D2 receptors and tyrosine hydroxylase in the basolateral amygdala were also measured. The result of the sucrose consumption test, sexual behaviour test and apomorphine test indicated a successful nonorganic erectile dysfunction model. Central infusion of a dopamine D2 receptor agonist increased intromission ratio in model rats. Lower expression levels of tyrosine hydroxylase and the dopamine D2 receptor in the basolateral amygdala were observed in rats with nonorganic erectile dysfunction. These results suggest that impairment of the dopamine D2 receptor pathway in the basolateral amygdala may contribute to the development of nonorganic erectile dysfunction.